(untitled) (Research, Society and Development, 2020)
Lettuce (Lactuca sativa L.) is considered the most consumed leafy vegetable in Brazil and in the world, contributing to the generation of jobs and income. In Brazil, the cultivation of this vegetable in a hydroponic system has grown, but there is no consensus between the electrical conductivity of the ideal nutrient solution (CEs) for cultivation, especially in regions. The objective was to evaluate the productive performance of two cultivars of lettuce according to different saline concentrations of the nutrient solution. A completely randomized design (DIC) was used in subdivided plots, with a 2x5 factorial scheme, with three replications. The lettuce cultivars were distributed in the plots (V1 = "Astra" and V2 "Bruma"). In the subplots, solutions with electrical conductivities (CEs) of: CEs1 = 0.5 were tested; CEs2 = 1.0; CEs3 = 1.5; CEs4 = 2.0 and CEs5 = 2.5 dS m-1. Kristalon orange 6-12-36, Calcium Nitrate and Tenso Cocktail were used to compose the nutrient solution. The fresh root mass of the cultivars Astra and Bruma behaved in a quadratic manner, increasing the CEs to 1.37 dS m-1. The length of the stem was influenced by the increasing salinity levels of the nutrient solution. There was an increase in the fresh weight of the aerial part up to the CEs of 1.31 dS m-1 for the cultivar Bruma and 1.03 dS m-1 for the cultivar Astra. The largest head circumference was estimated with the EC of 1.01 dS m-1 for Astra cultivar and 0.94 dS m-1 for Bruma cultivar. The CEs that provided the best production results were 1.31 and 1.03 dS m-1 for the cultivars Bruma and Astra respectively.